2019
DOI: 10.1038/s41467-019-12053-4
|View full text |Cite
|
Sign up to set email alerts
|

Bridging of Neisseria gonorrhoeae lineages across sexual networks in the HIV pre-exposure prophylaxis era

Abstract: Whole genome sequencing (WGS) has been used to investigate transmission of Neisseria gonorrhoeae , but to date, most studies have not combined genomic data with detailed information on sexual behaviour to define the extent of transmission across population risk groups (bridging). Here, through combined epidemiological and genomic analysis of 2,186 N. gonorrhoeae isolates from Australia, we show widespread transmission of N. gonorrhoeae within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
91
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(95 citation statements)
references
References 39 publications
4
91
0
Order By: Relevance
“…farA LOF mutations were associated with patient sex of sex partner (p = 5.06×10 -10 ; Fisher’s exact test) and site of infection (p = 1.76×10 -12 ; Fisher’s exact test) and overrepresented in cervical isolates: 33 out of 129 (25.6%) cervical isolates contained a farA LOF mutation compared to 117 out of 2246 urethral isolates (5.21%; OR = 6.25, 95% CI [3.90-9.83], p = 3.24×10 -13 ; Fisher’s exact test), 3 out of 106 pharyngeal isolates (2.83%; OR = 11.70, 95% CI [3.50-61.61], p = 3.80×10 -7 ; Fisher’s exact test), and 12 out of 246 rectal isolates (4.88%; OR = 6.66, 95% CI [3.19-14.80], p = 1.57×10 -8 ; Fisher’s exact test) (Figure 3). farA LOF mutations were prevalent also in our Australian validation dataset 38 (225/2180; 10.32%) and again associated with sex of sex partner (p < 2.20×10 -16 ; Fisher’s exact test) and site of infection (p < 2.20×10 -16 ; Fisher’s exact test) (Supplementary Figure 5). The phylogenetic distribution of farA LOF mutations overlapped with that of mtrA LOF mutations and indicated sustained transmission (Supplementary Figure 3).…”
Section: A Second Class Of Proton-dependent Efflux Pumps Appears To Cmentioning
confidence: 61%
See 3 more Smart Citations
“…farA LOF mutations were associated with patient sex of sex partner (p = 5.06×10 -10 ; Fisher’s exact test) and site of infection (p = 1.76×10 -12 ; Fisher’s exact test) and overrepresented in cervical isolates: 33 out of 129 (25.6%) cervical isolates contained a farA LOF mutation compared to 117 out of 2246 urethral isolates (5.21%; OR = 6.25, 95% CI [3.90-9.83], p = 3.24×10 -13 ; Fisher’s exact test), 3 out of 106 pharyngeal isolates (2.83%; OR = 11.70, 95% CI [3.50-61.61], p = 3.80×10 -7 ; Fisher’s exact test), and 12 out of 246 rectal isolates (4.88%; OR = 6.66, 95% CI [3.19-14.80], p = 1.57×10 -8 ; Fisher’s exact test) (Figure 3). farA LOF mutations were prevalent also in our Australian validation dataset 38 (225/2180; 10.32%) and again associated with sex of sex partner (p < 2.20×10 -16 ; Fisher’s exact test) and site of infection (p < 2.20×10 -16 ; Fisher’s exact test) (Supplementary Figure 5). The phylogenetic distribution of farA LOF mutations overlapped with that of mtrA LOF mutations and indicated sustained transmission (Supplementary Figure 3).…”
Section: A Second Class Of Proton-dependent Efflux Pumps Appears To Cmentioning
confidence: 61%
“…mtrC LOF mutations were significantly associated with site of infection (p = 6.49×10 -5 ; Fisher’s exact test) and were overrepresented particularly in cervical isolates: 16 out of 129 (12.4%) cervical isolates contained an mtrC LOF mutation compared to 82 out of 2249 urethral isolates (3.65%; OR = 3.74, 95% CI [1.98-6.70], p = 4.71×10 -5 ; Fisher’s exact test), 3 out of 106 pharyngeal isolates (2.83%; OR = 4.83, 95% CI [1.33-26.63], p = 0.00769; Fisher’s exact test), and 4 out of 246 rectal isolates (1.63%; OR = 8.52, 95% CI [2.67-35.787], p = 2.39×10 -5 ; Fisher’s exact test) (Figure 3b). Because our meta-analysis collection comprises datasets potentially biased by preferential sampling for drug-resistant strains, we validated our epidemiological associations on a set of 2186 sequenced isolates, corresponding to all cultured isolates of N. gonorrhoeae in the state of Victoria, Australia in 2017 38 . We again observed significant associations between mtrC LOF and sex of sex partner (p = 0.0180; Fisher’s exact test) as well as anatomical site of infection (p = 0.0256; Fisher’s exact test) (Supplementary Figure 5, Supplementary Text).…”
Section: Loss Of the Mtrcde Efflux Pump Is Associated With Cervical Imentioning
confidence: 99%
See 2 more Smart Citations
“…Chapter 2 has previously shown that S1 (previously described as G1) is sustained in 2012 and 2014 so it is interesting to note that isolates from New Zealand were collected in 2014 and 2015, suggesting a persisting heterosexual strain-type is present within multiple countries. Furthermore, S1 also appears to be present within a recent study investigating N. gonorrhoeae isolates from 2017 in the state of Victoria in Australia (referred to as clusters 24 and 91 in the study) (252). This finding highlights this strain has still remained prevalent within the Australian heterosexual population.…”
Section: Discussionsupporting
confidence: 54%